Negative expectations and measurable movement mechanics: a scoping review of the nocebo effect on motor performance - Burgos-Tirado, Jennifer; Léonard, Guillaume; Hakimi, Adrien; Vancraeynest, Deborah; Lelard, Thierry; Cozette, Maryne (Frontiers in Human Neuroscience, 2025)
IntroductionThe nocebo effect, where negative responses can occur as a result of negative expectations, has gained increasing attention in motor control research, with growing evidence highlighting its impact on both athletic and everyday movements. However, the specific methodologies used to induce nocebo effects on motor outcomes remain unexplored. This scoping review aimed to address three key questions: (1) What experimental protocols have been developed and used to elicit nocebo effects in motor performance in healthy individuals? (2) How are these effects assessed and measured? (3) What are the observed effects on motor outcomes?MethodsA scoping review was conducted following the PRISMA framework, searching PubMed, EBSCO, EMBASE, Cochrane, Web of Science, Scopus, and Google Scholar from inception to March 2025. Eighteen studies were included.Results and discussionVerbal instruction was the most common induction method (94.4 %), often combined with conditioning or visual cues. Motor tasks assessed gross skills, such as sprinting and cycling), with limited attention given to fine motor control. Outcomes were more frequently centered on performance measures (e.g., strength, endurance), with less emphasis on movement quality (e.g., coordination). Nocebo effects were observed in half of the studies impairing motor performance, including reduced force production, diminished endurance, disrupted postural stability and slower movement speed. The findings highlight methodological diversity in induction protocols and measurement methods. Future research should expand participant diversity, investigate fine motor tasks, and further explore the interplay between induction methods and motor outcomes.